Development and characterization of 14 microsatellite loci from an enriched genomic library of Eucalyptus camaldulensis Dehnh - da Silva, Janete Motta [UNESP]; Barbosa de Sousa, Adna Cristina; de Souza, Anete Pereira; Mori, Edson Seizo [UNESP]; Menezes Freitas, Miguel Luiz; Sebbenn, Alexandre Magno; Teixeira de Moraes, Mario Luiz [UNESP] (Springer, 2009)
Eucalyptus camaldulensis Dehnh is an Australian tree species which occurs in various climatic and environmental conditions and show large genetic diversity. Twenty five microsatellite markers were developed from a CT(8)-GT(8) enriched genomic library of E. camaldulensis. The number of alleles ranged from 4 to 13 (average of 8). The polymorphism information content (PIC) and the discriminating power (D) of each primer ranged from 0.37 to 0.88 (average of 0.72) and 0.48 to 0.99 (average of 0.84), respectively. The observed and expected heterozygosities ranged from 0.28 to 0.84 and 0.25 to 0.90, respectively. Four loci showed statistically significant from Hardy-Weinberg equilibrium after Bonferroni correction (P, (5%) < 0.0038). All polymorphic markers were tested for cross-amplification in 25 different Eucalyptus species. Those microsatellite loci will be useful to investigate questions of genetic diversity and structure, gene flow, mating system and ex situ genetic conservation of E. camaldulensis.
Keywords: Conservation genetic; Hardwoods; Molecular marker; Microsatellites; Cross-species amplification